THE BENEFITS CONFERRED BY MULTI-SPORT PARTICIPATION MAY NOT INCLUDE IMPROVED FUNCTIONAL AND PSYCHOLOGICAL READINESS FOLLOWING INJURY. Issue 7 (30th July 2021) - Kemper, Craig; Wagner, K. John; Carpenter, Connor M.; Wilson, Philip L.; Ellis, Henry B.
Background: Multi-sport participation has been advocated for youth as a means to foster athletic development and reduce over-use injury. Whether this sport variety may influence functional and psychological readiness after injury is unclear. Purpose: The purpose of this study was to compare presentation, and functional and psychological recovery between single sport and multi-sport pediatric athletes following an ACL reconstruction (ACLR). Methods: Following IRB approval, prospectively collected data in consecutive patients treated for ACL injury (1/2015-2/2017) in a pediatric sports medicine clinic was reviewed. Inclusion required primary ACLR. Injury and surgical data, patient reported outcome measures (PROM) including both functional (Pedi-IKDC) and psychological PROM (ACSI-28 and ACL-RSI), functional clearance data (Y balance testing), timing of return to play clearance, and any re-injuries were reviewed. Comparison of multi-sport and single sport athletes was performed using a Kruskal-Wallis test and ANOVA analysis followed by T-tests for multiple comparisons. Results: 81.5% of patients who underwent an ACL reconstruction were single sport athletes. Single sport athletes presented with a higher initial BMI (24.47 ± 5.67 vs 22.45 ± 3.81, p = 0.03) than multi-sport athletes. In this cohort, soccer players (89%) were more likely to be specialized compared to football (61%) or basketball players (69%, p<0.01). No differences between groups were noted regarding surgical procedures or concomitant injuries. While no significant differences were found between the groups in time to functional clearance or clearance scores, it was noted that only ¾ of single sport athletes returned to sports (74.0% vs 92.3%, p = 0.06). Reported confidence in functional and psychological recovery improved in both groups throughout rehabilitation (see Table 1). Multi-sport athletes in this cohort demonstrated no advantage in either phase of recovery. Conclusion: Although multi-sport participation has been established to improve athletic development, and decrease burnout and over-use injury; it may not confer advantages in comparison to the specialized athlete for functional or psychological recovery following ACL reconstruction. :